Synopsis and Qualitative Evaluation of a Treatment Protocol to Guide Systemic Group-Cognitive Behavioral Therapy for Misophonia - Jager, Inge; Vulink, Nienke; van Loon, Arnoud; van der Pol, Marthe; Schröder, Arjan; Slaghekke, Simone; Denys, Damiaan (Frontiers in Psychiatry, 2022)
Misophonia is a disorder in which patients suffer from anger or disgust when confronted with specific sounds such as those associated with eating or breathing, causing avoidance of cue related situations resulting in significant functional impairment. Functional magnetic resonance imaging studies suggest misophonia is associated with increased activity in the auditory cortex and salience network, which might reflect increased vigilance towards specific misophonia triggers. New treatments have been developed and investigated in the last years in which this vigilance plays an important role. This is a synopsis of the first group protocol for Cognitive Behavioral Therapy (G-CBT) for misophonia. We discuss the model of CBT for misophonia, provide a detailed guide to the treatment illustrated with a case study, discuss advantages, limitations and possible pitfalls by a qualitative evaluation of the protocol, and review evidence for the protocol.